Plan de marketing digital para la cafetería OMM SIRI de la ciudad de Loja, periodo 2018-2021 - Sánchez Sánchez, Jhonny Patricio (2019)
The herby investigation project has as general objective to develop a DIGITAL MARKETING PLAN TO BE IMPLEMENT IN THE OMM SIRI COFFEESHOP IN LOJA CITY, with the goal to contribute to the development and to make the business stronger according to the third sector where it belongs to. For the elaboration of the hereby investigation project I have presented a specific objective chart. First in relation with the external analysis in which an evaluation was conducted in order to find out the positive and negative aspects of the coffeeshop; by using the PESTEC analysis, study that allows the investigation of the levels affecting by political factors, economics, social, technology, ecology and market competition, by implementing the matrix (MEFE) of external factors in which the final result was 3.15, which means that the business is found above the measure of hard work, and therefore it must follow strategies to include external opportunities and to avoid the possible negative threats that can affect the business. Identify the most important opportunities which are, political stability, employment contracts, increase of the population of the Loja province at 7.8% in the following years, technology implementation and the use of household internet at 41.6%. Starting from the abovementioned opportunities we can determine the possibility to implement marketing strategies by the use of digital medium, by taking advantage of the technology to improve in the process of commerce and communication. The second objective is to study the marketplace, in which an interview was conducted to the coffeeshop’s manager, interview with the 5 employees of the business and 384 questioners made to customers of the coffeeshop, done by simple aleatory selection. During the internal business analysis, it was taken in consideration the functional areas and the corresponding factors of success, which allow us to develop advertisements strategies in order to promote the services provided by the coffeeshop. In this case in order to determine the strong and the weak areas we increase the matrix of evaluation of internal factors (MEFI) which gave a result of 2.90, which allows to identify that the main strong area is that the business fulfills all financial obligations, all employees have the correct working tools to performed their jobs, the business has enough working capital, the business’s “Know How” is unique and difficult to replicate. In the other hand as the weakness it was identify that the business does not provide with training programs for its employees, the bookkeeping is done in a traditional matter, there is no enough advertainments in the digital medium often use by the customers, and the business lacks a marketing plan. Therefore, to overcome its weaknesses it is advised to implement a communication plan ATL and/or BTL for Omm Siri Café. According to the analysis and in accordance to the objective that mentions the realization of a locational diagnostic we proceed to the elaboration of the FODA matrix, the INTERNAL-EXTERNAL matrix, allowed to identify that the business is located in the IV quadrant, within the region 1 that is growing and developing, therefore, the strategies must be of intensive integration. The MPC matrix or competitive profile where all the major coffeeshops are located that are competitors of Omm Siri are: “El Café Lojano”, “El Tamal Lojano”, El Cafecito Lojano”, and “El Apetito”. The coffeeshop Omm Siri, in the BCG matrix allows to identify and to know that the products of demand and market participation where it is determined that the coffeeshop Omm Siri has two star products with high acceptance in the market, three production cows of money that help the identified products in the inquiry can continue developing to reach higher in the participation of the market and finally 5 more identified products in the dog quadrant, that would be under the manager’s discretion to keep them or to replace them for new products. In the other hand the Ansoff matrix, it was identified that the coffeeshop Omm Siri, it is found in a current market with existing products, which means that the main business strategy is market penetration. In objective number four, in reference to the Digital Marketing Plan Proposal, the business philosophy and specific objectives were proposed for the implementation of the plan where it is proposed as the first objective: Position the Omm Siri Cafeteria in digital media through specialized photography to reach more clients who demanded their services at a cost of $ 1,250.00; In objective number two it is proposed to increase the participation of Omm Siri Cafeteria in the market through the presentation of products and the readjustment of new spaces for the taste and satisfaction of customers with a cost of $ 2 800.00 and for Objective number three is to apply a SEMM (Service Model Based on Marketing) to generate a competitive advantage in the market through a solid corporate image and the dissemination of its content in ATL and / or BTL media with a cost of $ 755.80. Therefore, for the fulfillment of the objectives, the total value of the digital marketing plan is: $ 4,805.80. Finally, the respective conclusions and recommendations are presented with the results obtained in the development of this digital marketing plan with the proposal of generating a competitive advantage and increasing its market share.